Erratum to "A Novel Approach for Computation of High-Order Axial Modes in a Gyrotron Resonator" [Dec 18 5505-5510] - Vishant; Bera, Anirban; Sinha, Ashok K.; Chandrashekhar (IEEE transactions on electron devices, 2019)
The authors would like to make a correction to the affiliation section of [1] on page 1, because one of the affiliations in [1] was missing. The correct affiliation section of [1] should read as follows.